Foundations of speech and hearing : anatomy and physiology - Hoit, Jeannette D. (Jeannette Dee), 1954-; Weismer, Gary; Story, Brad (San Diego, CA : Plural Publishing, Inc., 2022)
'This comprehensive textbook for undergraduate-level anatomy and physiology courses in communication sciences and disorders programs is neither oversimplified nor excessively detailed. The book is written with clinical endpoints in mind, and only those topics that are ultimately important to understanding, evaluating, and managing clients with speech, hearing, and swallowing disorders are covered. Drawing on material from the best-selling Preclinical Speech Science: Anatomy, Physiology, Acoustics, and Perception, Third Edition textbook (Hixon, Weismer, & Hoit, 2020), the authors have provided chapters that cover basic concepts in anatomy and physiology, each of the speech subsystems (respiratory, laryngeal, velopharyngeal-nasal, and pharyngeal oral), the auditory system, swallowing physiology, and neural structures and mechanisms that support speech/language, hearing, and swallowing. The text was carefully crafted to meet the needs of entry-level university students and the figures were designed to feature the key elements of the concepts discussed in the text'--
Introduction to basic concepts -- Respiratory structure and function -- Laryngeal structure and function -- Velopharyngeal-nasal structure and function -- Pharyngeal-oral structure and function -- Auditory system structure and function -- Swallowing structure and function -- Brain structures and mechanisms for speech/language, hearing, and swallowing.
Includes bibliographical references and index.
Description based on online resource; title from electronic title page (ProQuest Ebook Central, viewed August 10, 2023).
Keywords: Speech -- Physiological aspects; Speech perception; Speech disorders; Respiratory organs -- Anatomy; Speech -- physiology; Speech Perception; Speech Disorders; Respiratory System -- anatomy & histology; Parole -- Aspect physiologique; Perception de la parole; Troubles de la parole; Speech perception; Speech disorders; Speech -- Physiological aspects